Parking as a loss leader at shopping malls. (September 2016) - Ersoy, Fulya Yuksel; Hasker, Kevin; Inci, Eren
Highlights: Shoppers choose between car and bus in getting to a suburban mall. There are external discomfort costs in buses due to crowdedness. The mall suffers from these costs since shoppers taking the bus impose crowding costs on each other. To internalize the costs, the mall embeds the external costs in the price of the good. It then sets a parking fee less than its marginal cost (loss-leader pricing). Abstract: This paper investigates the pricing of malls in an environment where shoppers choose between a car and public transportation in getting to a suburban mall. The mall implicitly engages in mixed bundling; it sells goods bundled with parking to shoppers who come by car, and only goods to shoppers who come by public transportation. There are external costs of discomfort in public transportation due to crowdedness. Thus, shoppers using public transportation deter each other. The mall internalizes these external costs, much like a policy maker. To do so, it raises the sales price of the good and sets a parking fee less than parking's marginal cost. Hence, parking is always a loss leader. Surprisingly, this pricing scheme is not necessarily distortionary.